Case Markers In Ugaritic Language A Comparative Study (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This research is done to study the case markers in the Ugaritic language and see the syntactic positions of expressions in the sentence, by applying the comparatives method. We show in this study that the noun is used in the case marked expressions, i. e its case changes in accordance with to its place in the sentence and in accordance to the functional element preceding it, so that it could be nominative, accusative or object to a preposition. And our study shows that the present verb could be also cased-marked: it can be nominative, accusative or jussive, and that the case markers can be in this sematic language: case markers, letters, a vowel deletion, or nun- deletion too. Because the Ugaritic language has three symbols for the Hamza with short sounds, they correspond to the case markers in Arabic and the case shows itself in (a) (u) and (i) showing themselves in final position clearly. By comparing the Ugaritic expressions and the Arabic ones we have noticed that we have three case markers, namely (a) (u) and (i). This study alludes to the case markers common in both the language and to those that are different too.